Labour market competition for public health graduates in the United States: A comparison of workforce taxonomies with job postings before and during the COVID‐19 pandemic. (24th February 2021) - Krasna, Heather; Czabanowska, Katarzyna; Beck, Angela; Cushman, Linda F.; Leider, Jonathon P.
Abstract: A strong public health workforce (PHW) is needed to respond to COVID‐19 and public health (PH) issues worldwide. However, classifying, enumerating, and planning the PHW is challenging. Existing PHW taxonomies and enumerations focus on the existing workforce, and largely ignore workforce competition for public health graduates (PHGs). Such efforts also do not utilize real time data to assess rapid changes to the employment landscape, like those caused by COVID‐19. A job postings analysis can inform workforce planning and educational program design alike. To identify occupations and industries currently seeking PHGs and contrast them with existing taxonomies, authors matched existing PHW taxonomies to standardized occupational classification codes, then compared this with 38, 533 coded, US job postings from employers seeking Master's level PHGs from 1 July 2019 to 30 June 2020. Authors also analysed 24, 516 postings from March 2019 to October 2019 and compared them with 24, 845 postings from March 2020 to October 2020 to assess changing employer demands associated with COVID‐19. We also performed schema matching to align various occupational classification systems. Job postings pre‐COVID and during COVID show considerable but changing demand for PHGs in the US, with 16%–28% of postings outside existing PHW taxonomies, suggesting labour market competition which may compound PHW recruitment and retention challenges.